2016
DOI: 10.3791/53814
|View full text |Cite
|
Sign up to set email alerts
|

Cultivate Primary Nasal Epithelial Cells from Children and Reprogram into Induced Pluripotent Stem Cells

Abstract: Nasal epithelial cells (NECs) are the part of the airways that respond to air pollutants and are the first cells infected with respiratory viruses. They are also involved in many airway diseases through their innate immune response and interaction with immune and airway stromal cells. NECs are of particular interest for studies in children due to their accessibility during clinical visits. Human induced pluripotent stem cells (iPSCs) have been generated from multiple cell types and are a powerful tool for mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Dampening the “innate immune response” to smoking played a critical role in modifying pulmonary inflammation and lung remodeling, which might slow the progression of COPD [ 30 ]. Nasal epithelial cells are involved in many airway diseases, including asthma and COPD, through their “innate immune response” and interaction with immune and airway stromal cells [ 31 ]. Bush et al found that genes important in “lung development” and early wheezing were implicated in COPD [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dampening the “innate immune response” to smoking played a critical role in modifying pulmonary inflammation and lung remodeling, which might slow the progression of COPD [ 30 ]. Nasal epithelial cells are involved in many airway diseases, including asthma and COPD, through their “innate immune response” and interaction with immune and airway stromal cells [ 31 ]. Bush et al found that genes important in “lung development” and early wheezing were implicated in COPD [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Being exposed, the olfactory nerve is a highly vulnerable organ and damage to this nerve results in hyposmia and anosmia in a large number of patients. Although hTMSCs are promising candidates for iPSC induction or as donor cells for such patients, only a few studies using hTMSCs have been reported [1,3]. An important road block currently faced is the low success rate of stem cell differentiation and iPSC induction.…”
Section: Discussionmentioning
confidence: 99%
“…3 Nasal epithelial cells (NECs) were collected from beneath the inferior turbinate using a cytology brush according to published techniques. 5 Importantly, cells were cultured for 1-4 weeks including two passages to limit effects of in vivo exposures (environmental, medications) on cellular readouts. To measure IL-17A responsiveness, passaged NECs were plated in 24-well plates, allowed to reach confluence and then treated with medium alone or IL-17A (100 ng/ml) for 18-20 h. Production of the IL-17A-induced chemokine, CXCL1 (GROα), was assessed in supernatants by ELISA.…”
Section: Following Irb Approval By Cincinnati Children's Hospital Med...mentioning
confidence: 99%
“…Air pollutant exposure was estimated based on mean concentration of elemental carbon attributable to traffic (ECAT) exposure at birth and current address 3 . Nasal epithelial cells (NECs) were collected from beneath the inferior turbinate using a cytology brush according to published techniques 5 . Importantly, cells were cultured for 1–4 weeks including two passages to limit effects of in vivo exposures (environmental, medications) on cellular readouts.…”
Section: Figurementioning
confidence: 99%